A comparison of electric power output of CO2 Plume Geothermal (CPG) and brine geothermal systems for varying reservoir conditions. (15th February 2015) - Adams, Benjamin M.; Kuehn, Thomas H.; Bielicki, Jeffrey M.; Randolph, Jimmy B.; Saar, Martin O.
Highlights: CO2 has less pressure losses in a sedimentary geothermal reservoir than brine. CO2 produces more power at shallower depths and lower permeabilities than brine. CO2 is a better working fluid in secondary Rankine cycles than R245fa. Increasing the well diameters dramatically increases geothermal power production. Abstract: In contrast to conventional hydrothermal systems or enhanced geothermal systems, CO2 Plume Geothermal (CPG) systems generate electricity by using CO2 that has been geothermally heated due to sequestration in a sedimentary basin. Four CPG and two brine-based geothermal systems are modeled to estimate their power production for sedimentary basin reservoir depths between 1 and 5 km, geothermal temperature gradients from 20 to 50 °C km −1, reservoir permeabilities from 1 × 10 −15 to 1 × 10 −12 m 2 and well casing inner diameters from 0.14 m to 0.41 m. Results show that CPG direct-type systems produce more electricity than brine-based geothermal systems at depths between 2 and 3 km, and at permeabilities between 10 −14 and 10 −13 m 2, often by a factor of two. This better performance of CPG is due to the low kinematic viscosity of CO2, relative to brine at those depths, and the strong thermosiphon effect generated by CO2 . When CO2 is used instead of R245fa as the secondary working fluid in an organic Rankine cycle (ORC), the power production of both the CPG and the brine–reservoir system increases substantially; for example, by 22% and 20% for subsurface brine and CO2 systems, respectively, with a 35 °C km −1 thermal gradient, 0.27 m production and 0.41 m injection well diameters, and 5 × 10 −14 m 2 reservoir permeability.